Designing the learning trajectory for the topic of circles through a tambourine context - Juniarti, Anita; Jojo, Zingiswa; Prahmana, Rully Charitas Indra (Universitas Papua, 2022)
A tambourine is one of the musical instruments commonly used in Islam. It is also used in an extracurricular activity in various schools so that many students are familiar with the instrument, making it relevant for learning mathematics. Furthermore, there is an approach to learning mathematics called Indonesian Realistic Mathematics Education (IRME), where students start the learning with contexts close to their lives. This study aims to design a learning trajectory using the IRME approach with a tambourine context to support students' understanding of circles. This learning progresses from the informal stage to the formal through the IRME approach. The study applied design research with three stages: preliminary design, design experiments, and retrospective analysis. The research subjects were 19 six-grade students in one of the elementary schools in Balangan, South Kalimantan, Indonesia. The instruments used were videos to observe the learning process and how students work on the questions given, photos to reference students’ work, and a test in a student worksheet to obtain data on students’ work. The results reveal the learning trajectory practised using the tambourine as the context seen in the student's daily activities. The learning trajectory consists of four events: assembling the tambourine, drawing an illustration of the tambourine, listing the parts of a circle, and solving a problem related to the parts of the circle. In addition, this study also shows that learning trajectory activities have essential roles in supporting students' understanding of the concept of a circle.